2023
DOI: 10.1007/s00784-023-04868-9
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical study of injectable dextrin-based hydrogel as a carrier of a synthetic bone substitute

Abstract: Objectives This study aimed to improve the performance and mode of administration of a glass-reinforced hydroxyapatite synthetic bone substitute, Bonelike by Biosckin® (BL®), by association with a dextrin-based hydrogel, DEXGEL, to achieve an injectable and moldable device named DEXGEL Bone. Methods Twelve participants requiring pre-molar tooth extraction and implant placement were enrolled in this study. BL® granules (250–500 µm) were administered to 6 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Background information from each trial was summarized including clinical phase, condition, controls used, and follow-up. Studies were conducted in Spain [35], Mexico [36], Norway [37], the Czech Republic [38], Italy [39][40][41], Western Australia (NCT01742260), and Spain and Portugal [42]. One trial was reported in three publications [39][40][41].…”
Section: Overview Of Published Clinical Trials With Mscs and Scaffold...mentioning
confidence: 99%
See 3 more Smart Citations
“…Background information from each trial was summarized including clinical phase, condition, controls used, and follow-up. Studies were conducted in Spain [35], Mexico [36], Norway [37], the Czech Republic [38], Italy [39][40][41], Western Australia (NCT01742260), and Spain and Portugal [42]. One trial was reported in three publications [39][40][41].…”
Section: Overview Of Published Clinical Trials With Mscs and Scaffold...mentioning
confidence: 99%
“…One trial was reported in three publications [39][40][41]. Two clinical trials were at Phase I [35] (NCT01742260), two were at Phase I/II [37,39], one was at Phase IIa [38], and phase was not reported in one clinical trial [36,42]. The studies were prospective, open, non-randomized [35,37,[39][40][41], randomized [36,42], interventional (NCT01742260), and in particular, one trial was multicentric [39][40][41].…”
Section: Overview Of Published Clinical Trials With Mscs and Scaffold...mentioning
confidence: 99%
See 2 more Smart Citations
“…The stability of primary implants was analyzed using the implant stability coefficient method; the study finally concluded that the hydrogel reinforcement material was easy to handle and showed good defect healing effect. 208 Currently, only a few clinical trials have examined the application of hydrogels in bone repair, which poses a challenge for future clinical transformation.…”
Section: Application Of Self-healing Hydrogels For Bone Defect Repairmentioning
confidence: 99%